Cryogenic Technologies in Production of Pharmaceutical, Cosmetic, Agrotechnical Formulations and Biologically Active Food Additives - Osetsky, A. I.; Grischenko, V. I.; Goltsev, A. N.; Kravchenko, M. A.; Stryuchkova, E. V. (Problems of Cryobiology and Cryomedicine, 2009)
There has been considered the process of low temperature molecular fractionation of biological raw materials of plant and animal origins using contemporary cryogenic technologies: rapid freezing in nitrogen cryotunnels, cryodispersion, cryosublimation fractionation, extraction with condensed gases. The variants of using the resulted fractions in the production of pharmaceutical, veterinary, agrotechnical, cosmetic formulations and highly vitaminized food products are under discussion.